Corporate Outsourcing Evaluation Financial Mechanisms - Tsygalov, Yury M.; Dorozhkina, Ekaterina E.; Dorozhkin, Alexey V.; Ordinartsev, Igor I. (Journal of Reviews on Global Economics, 2018)
The subject matter of the article is the outsourcing efficiency evaluation mechanisms. The purpose of the article is to suggest the outsourcing efficiency evaluation mechanism accounting for the interests of all participants of a corporation restructuring and for the risks of company transformation. Research methodology is based on the application of systemic and institutional approaches, induction and analysis, comparison and generalization. The outsourcing efficiency evaluation methods have been analyzed. The known evaluation methods are found to have industrial focus, which determines selection of such efficiency criteria as seasonal personnel optimization, logistics improvement, and reduction of information system failures. Such standard efficiency criteria as production costs reduction, improvement of rendered services quality, and higher production processes balance are widely applied. Methods based on financial indicators of a company transformation are rarely applied. The mechanisms of outsourcing efficiency evaluation have little concern for the key commercial activity task of company value increase. A major drawback of the known approaches is the methods' focus on the companies ordering outsourcing. The impact of risks related to switching to outsourcing is nearly never accounted. Suggestions are made on generation of an outsourcing efficiency evaluation mechanism based on @Risk indicator, which accounts for changes of indicators of all participants of a restructuring process. Any criterion relevant for a certain company may be used as an efficiency indicator. However, free cash clow at risk (FCF@Risk) is suggested to be used as the main efficiency evaluation indicator. An outsourcing project is deemed efficient if ΔFCF@Risk is positive after switching to outsourcing.